The Use of Music and Music Therapy in Ameliorating Depression Symptoms and Improving Well-Being in Nursing Home Residents With Dementia - Ray, Kendra D.; Götell, Eva (Frontiers in Medicine, 2018)
Background: Studies have shown music therapy can improve depression symptoms in dementia and the use of music-based interventions show promise to have positive impacts on wellbeing. However, few studies show the influence of a music intervention led by certified nursing assistants (CNAs) trained by music therapists to address depression and wellbeing in individuals with dementia. Methods: Credentialed music therapists administered two-weeks of music therapy, a 3-day training to CNAs, followed by two-weeks of music-based interventions for 62 nursing home residents with moderate dementia, then measured depression symptoms using the Cornell Scale for Depression. We obtained video consent for 26 of the 62 residents who were video recorded receiving CNA-facilitated music-based caregiving activities. Video data was analyzed and well-being was rated with the Music in Dementia Assessment Scale. Results: A repeated measures ANOVA revealed that mean depression scores differed statistically significantly between time points. Residents’ depression symptoms significantly declined following music therapy, increased during a two-week wash-out period, but appeared to stabilize following the music-based intervention. A video analysis and paired sampled t-test demonstrated a significant improvement in wellbeing in residents who engaged in music with movement. Wellbeing improved slightly, but not significantly for residents who participated in the singing intervention. Conclusion: Findings suggest that music therapy can significantly decrease depression symptoms in nursing home residents with dementia. Music activities designed by music therapists and facilitated by CNAs can help sustain the reduction of depression symptoms and improve wellbeing in nursing home residents with moderate dementia.